2016
DOI: 10.1037/aca0000051
|View full text |Cite
|
Sign up to set email alerts
|

Truths about beauty and goodness: Disgust affects moral but not aesthetic judgments.

Abstract: Aesthetic judgments typically involve assessments of one's own responses and thus are partly or largely subjective. Moral judgments may seem otherwise, but their susceptibility to influence by factors extrinsic to the object of judgment-notably, by irrelevant sensations of disgust-has led some to argue that moral and aesthetic judgments are functionally alike, a view consistent with philosophical arguments and neuropsychological evidence. We examined the behavioral consequences of this view by adapting Eskine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Hypothesis H8 concerned the relationship between aesthetic needs and sensitivity to disgust. Although Rabb et al [ 80 ] found that inducing a state of disgust did not influence aesthetic judgement (but did influence moral judgment), no research publication has reported on the relationship between trait disgust and aesthetic needs. We theorized that individuals with high aesthetic needs are also more sensitive to potentially ugly and disgusting experiences [ 34 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothesis H8 concerned the relationship between aesthetic needs and sensitivity to disgust. Although Rabb et al [ 80 ] found that inducing a state of disgust did not influence aesthetic judgement (but did influence moral judgment), no research publication has reported on the relationship between trait disgust and aesthetic needs. We theorized that individuals with high aesthetic needs are also more sensitive to potentially ugly and disgusting experiences [ 34 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as in Parsons, these results are not found in later stages in our data. The Rabb et al (2016) study shows us that in adults who have drunk a bitter liquid, moral evaluations are worse. However, evaluations of the paintings that represent morally negative scenes are not seen as negative in themselves, providing evidence that in adults there is a differentiation between these two types of judgment: aesthetic and moral.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite the importance of assessing interindividual differences in the intensity of responses to aesthetic stimuli, this aspect is not reflected in previous scales. In addition, the AReA focuses on responses to aesthetic stimuli, excluding responses to nonaesthetic beautiful stimuli such as talent, virtue, or morality, included in both the EBS and ABE, which may operate differently (Came, 2012; Güsewell & Ruch, 2012; Hawley-Dolan & Young, 2013; Rabb et al, 2016; Wang et al, 2015). Another way in which the AReA differs from these previous measures is the inclusion of items that together cover both different content domains such as visual art, dance, and music, as well as different response domains such as affective, cognitive, behavioral, and physiological aspects of how a person responds to a particular stimulus (Brattico et al, 2013; Schlotz et al, 2021).…”
Section: The Aesthetic Responsiveness Assessment (Area)mentioning
confidence: 99%